SELECTION OF AN EFFECTIVE STARCH OXIDIZER FOR THE PURPOSE OF USE OF ITS MODIFICATIONS IN PAPER SIZING (European Journal of Interdisciplinary Research and Development, 2023)
This article presents the results of studying the properties of corn starch in the process of oxidation with hydrogen peroxide in the presence of FeSO4. It has been established that an increase in the concentration of solids in oxidized starch dispersions also leads to an increase in the strength of the jelly. At the same time, the equilibrium moisture content of oxidized corn starch has been somewhat lower than that of native starch samples.